KAJIAN AYAT MAKKIYAH DAN MADANIYAH MENURUT PEMIKIRAN ORIENTALIS DAN OKSIDENTALIS - Supriatna, Papay (Institut PTIQ Jakarta, 2024)
Understanding the differences between Makkiyah and Madaniyah verses in the study of Qur'anic interpretation is essential to understand the evolution of Islamic teachings and their application in various contexts. The Makkiyah verses, which were revealed before the Hijrah, emphasize the basic teachings of faith, life after death, and morality, while the Madaniyah verses, which were revealed after the Prophet Muhammad migrated to Medina, focus on social, legal, and political aspects. This study aims to analyze the orientalist and occidentalist views on these differences and their impact on the understanding of Qur'anic texts. This study uses a descriptive qualitative approach with thematic analysis of primary and secondary sources, including classical and modern interpretations as well as orientalist and occidentalist works. The results show that orientalists emphasize more historical-critical aspects in examining these verses, while occidentalist thinkers focus on contextualizing Islamic teachings with Western social theory. An understanding of the differences between Makkiyah and Madaniyah verses is essential for refuting orientalist and occidentalist claims, as well as for adapting interpretations in the face of contemporary social challenges.